Credit derivatives and stock return synchronicity - Bai, Xuelian; Hu, Nan; Liu, Ling; Zhu, Lu (Journal of Financial Stability, 2017)
The role of credit default swaps (CDS) in the 2008 financial crisis has been widely debated among regulators, investors, and researchers. While CDS were blamed for destabilizing the financial system, they remain effective tools for hedging credit risk, especially for major banks, and produce positive informational externalities to market participants. This paper examines whether the introduction of CDS enhances the amount of firm-specific information impounded in stock prices. We use stock return synchronicity to measure the amount of firm-specific information reflected in stock prices, with more firm-specific information being associated with a lower level of synchronicity. We find that a firm’s stock return synchronicity decreases after the commencement of CDS trading. This finding is robust to different model specifications, synchronicity measures, and endogeneity controlling methodologies. Furthermore, the decrease in stock return synchronicity is more pronounced for CDS firms with higher credit risk. Overall, our evidence supports the positive role of CDS in improving informativeness of stock prices.